Nanocasting construction of few-graphene-layers carbon with tunable layer spacing as ultra-stable anode for sodium-ion batteries. (1st July 2022) - Li, Hong-Ji; Shen, Shao-Peng; Tang, Geng; Li, Jing-Jing; Lyu, Xue-Feng; Zhu, Li-Jun; Jiang, Fei; Chen, Yi-Qian; Yue, Junpei; Chen, Zhe
Highlights: The few-graphene-layers carbon with a tunable layer spacing for SIBs were prepared via a simple nanocasting method. The optimized GLC as anode for SIBs exhibits high reversible capacity, rate capability and excellent cycling stability. The suitable spacing layer and pore structure are both essential for thermodynamic and kinetic processes of Na + storage. Abstract: Sodium-ion batteries (SIBs) are competitive candidates to the next-generation batteries with respect to the abundant Na resources and potentially low cost. Exploring novel anodes for SIBs is essentially important for their practical application. Here, we successfully constructed few-graphene-layers carbon with controllable layer spacing via a simple nanocasting method, which offered a reproducible model to study the Na + storage mechanisms in carbon materials. In combination with state-of-the-art characterization technologies involving materials and electrochemistry, interlayer spacing was a critical factor and the one with 0.40 nm exhibited the superior electrochemical performance, e.g. a high reversible capacity of 288 mA h g −1 at 20 mA g −1, rate capacity (120 mA h g −1 at 5 A g −1 ), an excellent capacity retention (barely loss; ∼200 mA h g −1 after 1000 cycles at 100 mA g −1 ). This study correlated the microstructure of carbon materials with electrochemical performance and provided a design principle for carbon-based anodes for SIBs. Graphical abstract: Image, graphical abstract Few-graphene-layers carbon as anodes for sodium-ion batteries are successfully prepared by a simple nanocasting method. The suitable pore structure and interlayer spacing enable the high and fast Na + storage, and offer the good structural stability during the charge/discharge and outstanding long-cycle performance (barely loss; ∼200 mA h g −1 after 1000 cycles at 100 mA g −1 ).